A comparative analysis of risk measures: A portfolio optimisation approach. Issue 3 (3rd July 2019) - Gilbert, Evan; Meiklejohn, Luke
ABSTRACT: Investment portfolios are typically created to minimise the level of risk for a required level of return. This paper highlights the importance of the choice of risk metric in this process. The theoretical nature of volatility as a risk measure is reviewed, as are those of three commonly used alternatives: Conditional Value at Risk (CVaR), Omega Ratio and the Wang Transform Risk Measure. The Wang measure is a new measure in a multi-asset portfolio management context. The practical implications of the application of these four different risk metrics are then reviewed in the context of a South African multi-asset class portfolio targeting CPI + five per cent. The results illustrate that the choice of risk measure results in significantly different asset allocation (both strategically and tactically) and related performance outcomes. This highlights the importance for investment managers of the selection of risk measures in a multi-asset portfolio construction context.